Design and Control for the Buck-Boost Converter Combining 1-Plus-D Converter and Synchronous Rectified Buck Converters - Jeevan Naik (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In this paper, a design and control for the buck-boost converter, i.e., 1-plus-D converter with a positive output voltage, is presented, which combines the 1-plus-D converter and the synchronous rectified (SR) buck converter. By doing so, the problem in voltage bucking of the 1-plus-D converter can be solved, thereby increasing the application capability of the 1-plus-D converter. Since such a converter operates in continuous conduction mode inherently, it possesses the nonpulsating output current, thereby not only decreasing the current stress on the output capacitor but also reducing the output voltage ripple. Above all, both the 1-plus-D converter and the SR buck converter, combined into a buck–boost converter with no right-half plane zero, use the same power switches, thereby causing the required circuit to be compact and the corresponding cost to be down. Furthermore, during the magnetization period, the input voltage of the 1-plus-D converter comes from the input voltage source, whereas during the demagnetization period, the input voltage of the 1-plus-D converter comes from the output voltage of the SR buck converter.